PENGARUH MODEL CTL TERHADAP KETERAMPILAN MENULIS PUISI SISWA KELAS SEKOLAH DASAR - rusti yarso (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThe problem in this study was "How does the influence of the application of contextual teaching and learning models on poetry writing skills of fifth grade students of Elementary School 24Pontianak City?". The method used in this research was the experimental method used in this research was Quasi experimental design with the form of Nonequivalent control group design. The population was all students of class V which amounted to 63 people, while the sample was class V A as a control class totaling 32 students and class V B as the experimental class amounted to 31 students. Based on the data analysis, the results of the experimental class post-test average 80,31 and the control class post-test average 72,75. The results of t-test obtained tcount = 4.372 and ttable α = 5% (with  dk 31 + 32-2 = 61) is 1.671, which means tcount (4.372 )> t table (1.671), then Ha is accepted. The results of the calculation of the effect size obtained ES = 0.78. It can be said that the application of the contextual teaching and learning model has an influence with the medium category on poetry writing skills of the fifth grade students of 24 Elementary School 24Pontianak Kota..Keywords: Contextual Teaching and Learning, Influence, Poetry Writing Skills